Marine economy - the new development trend of mankind in the \(21^st\) century - Nguyen, Tac An (Vietnam Journal of Marine Science and Technology, 2021)
The article introduces the basic understanding of the marine economy and why humankind has to turn to the sea and the ocean in the 21st century, sea and ocean use, and approaches to exploitation and governance of ocean, marine, coastal and island economy for sustainable development. It also analyses international and regional lessons learned, the actual situation of marine economic growth in Vietnam in the past 30 years, some management and exploitation solutions (integrated management, ecological security, international cooperation,...) for socioeconomic development, sovereignty protection and territorial security in the East Vietnam Sea in the current complex context.